Carboniferous porphyry Cu (-Au) mineralization of the West Junggar region, NW China: the Shiwu example. Issue 9 (4th July 2017) - Li, ChangHao; Shen, Ping; Pan, HongDi; Huang, Wei; Cao, Chong
ABSTRACT: The West Junggar region, located in the Central Asian Orogenic Belt (CAOB), is characterized by extensive Carboniferous magmatism and porphyry Cu (-Au) deposits. The Shiwu porphyry Cu-Au deposit, located in the east of the Barluk Mountains, the West Junggar region, is not only a newly discovered deposit but also a representative porphyry Cu-Au deposit in this area. The volcanic rocks (including andesite and tuff) and intrusive rocks (including diorite, quartz diorite, quartz diorite porphyry, and tonalite porphyry) occurred in the Shiwu area and the mineralization associated with the quartz diorite porphyry. The secondary ion mass spectrometry (SIMS) zircon U–Pb ages of quartz diorite porphyry and tonalite porphyry are 310.4 ± 2.3 Ma and 310.1 ± 2.4 Ma, respectively, indicating that the Shiwu deposit is related to the Late Carboniferous magmatism. Intrusive rocks, which were characterized by the enrichment of large ion lithophile elements (LILEs) and pronounced negative high field strength elements (HFSEs), belong to the calc-alkaline or tholeiitic series. Their ( 87 Sr/ 86 Sr)i, ( 143 Nd/ 144 Nd)I, and ε Nd( t ) values range from 0.703569 to 0.704311, 0.512488 to 0.512512, and 4.9 to 5.3, respectively. Volcanic rocks, which belong to the calc-alkaline series, have similar geochemical features as the intrusive rocks, and their ( 87 Sr/ 86 Sr)i, ( 143 Nd/ 144 Nd)i, and ε Nd( t ) values, respectively, are 0.703704–0.704071, 0.512520–0.512542, and 5.49–5.92. These characters indicate that the igneous rocks in the Shiwu area derived dominantly from the mantle and formed in an island arc setting. These characters also further confirmed that the Barluk Mountains is still in an island arc setting in the Late Carboniferous and the accretionary orogenesis can exist until 310 Ma at least.